2019
DOI: 10.3889/oamjms.2019.037
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between the Duration of Playing Gadget and Mental Emotional State of Elementary School Students

Abstract: BACKGROUND:Technology has provided a type of facility in the world that currently makes the world like a virtual globe. One of the technologies currently used by humans is gadgets. Generally, children and adolescents nowadays often use gadget excessively. They use it excessively which may affect their social and emotional functions.AIM:This study aims to determine the relationship between the duration of playing gadget and mental-emotional state of elementary school students.METHODS:This study uses Strength an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 2 publications
4
32
0
10
Order By: Relevance
“…Hasil penelitian lain Rahmawati (2018) mengatakan bahwa kurangnya pengawasan dan perhatian dari orang tua, anak lebih menghabiskan waktu untuk bermain gadget untuk game dan menonton video. Durasi dan frekuensi penggunaan gadget berkorelasi dengan mental emosional pada siswa sekolah dasar (Wahyuni, Siahaan, Arfa, Alona & Nerdy, 2019).…”
unclassified
“…Hasil penelitian lain Rahmawati (2018) mengatakan bahwa kurangnya pengawasan dan perhatian dari orang tua, anak lebih menghabiskan waktu untuk bermain gadget untuk game dan menonton video. Durasi dan frekuensi penggunaan gadget berkorelasi dengan mental emosional pada siswa sekolah dasar (Wahyuni, Siahaan, Arfa, Alona & Nerdy, 2019).…”
unclassified
“…About 61% parents feels that their children are more interested and curious about changing social trends. 11 Miriam E Bar conducted a survey which showed that children's have learned pro social content of the television program and were able to apply that learning to a number of real-life situations. According to this study 16 % of parents feels that they are getting relevant useful information and 49% of study group disagree for that.…”
Section: Discussionmentioning
confidence: 99%
“…Despite that, the majority of the studies discovered the high-frequency use of mobile phones and the internet are closely associated with depression and anxiety [67,69,70,[72][73][74]76]. The influence of mobile device usage can be a severe problem for teenagers which studies have concluded that overuse may cause suicidal and self-harming ideation [71,72,79].…”
Section: Well-beingmentioning
confidence: 99%
“…Online First Some studies also aim to focus on validating theories and hypotheses [67,69,74]. This method requires a large number of respondents to perform statistical analysis and to draw conclusions based on the derived hypothesis.…”
Section: Eai Endorsed Transactions On Pervasive Health and Technologymentioning
confidence: 99%